TIC’S como estrategias para la comunicación de las secretarias del Colegio Nacional San Juan - Castro Torres, Nohely Valeria (2022)
The purpose of this case study is to establish ICTs as communication strategies for the secretaries of Colegio Nacional San Juan, located in the San Juan de Puebloviejo parish. It is of vital importance to carry out case studies of this nature since the secretary currently plays an important role in the development of modern societies, has achieved roles and functions beyond the traditional ones, which makes her a professional with skills and own skills and techniques for the work performed. With the development of these strategies, the main beneficiaries are the secretaries of the institution and it is expected that after the project is carried out, they will be able to design and implement programs and projects to strengthen the campus, guide the formulation of development plans and programs that can support the preparation of strategic plans, action plans and investment projects strengthened in ICT guidelines, coordinate and manage resources, promote the use of information technologies. The development of this case study is feasible since they have the resources and the necessary disposition to fulfill the stated objective, likewise the study population is available to learn and take advantage of the new tools that are sought to be provided to improve the quality of their work, as well as the director of the campus since they provide the corresponding authorization to carry out the study.